Salesforce motivation compensation and incestives - Pekerkan, S. Didem Öztunç. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1992., 1992)
The objective of this research is to provide an extensive literature review on motivation in general and salesforce motivation in detail: and to conduct an empirical study on motivation by focusing on expectancy theory of motivation. The Iiterature review includes motivation in general, sales force motivation, theories of motivation and salesforce moti vat ion, expectancy theory of motivation, sales force compensation and incentives. The field study of the research is done in two parts: The first part is a quantitative study in the Turkish pharmaceutical industry in the context of a case study. The components of motivation, the total quantifiable amount of motivation, the determinants of components of motivation and regional differences in general level of motivation of salespeople are empirically analyzed. The implicative power of the study is strengthened by focusing upon "sales incentives" in relation to reward systems in motivation. The sales force population of a pharmaceutical firm is chosen for data gathering in this quantitative study. The second part is employing a qualitative design in other industries. In this qualitative study, motivation, compensation, and incentive practices of firms in banking, insurance, pharmaceutical, and consumer goods industries are explored through personal interviews with the managers. The Statistical Package for Social Sciences is utilized for data analysis, through frequencies, crosstabulation, correlation, and t-test analyses. The findings of the qualitative study are analyzed by content analysis. The major conclusions of the study are that the most valued reward is personal growth; salespeople are, most satisfied with liking and respect they receive at work; the marginal util i ty of internally-mediated rewards is proven; there are no significant relationships among individual factors and motivational components; salespeople have an average level of motivation; there is a significant relationship and consistency among motivation measured through the model introduced in the study and direct measure of motivation; there are no major differences among regions and groups with respect to the motivational variables; salespeople mostly prefer combination compensation plans; the most preferred incentives are life insurance, casualty insurance, and personal use of company car; and salespeople prefer group or regional achievement and individual achievement as criteria for incentive awards. Two major contributions of the study are detecting the total amount of motivation, extrinsic and intrinsic motivation of salespeople in a pharmaceutical firm to compare with direct measures of motivation of the same salespeople as behavioral intentions and analyzing regional differences in motivation. An additional theoretical contribution stemming from the qualitative study is the contradiction with the well-known theories of motivation and practices of compensation regarding the compensation practices in different industries, namely insurance, consumer goods, and pharmaceutical industries.
Keywords: Motivation (Psychology); Employee motivation.; Incentives in industry.